Editorial: antigenic response to CT‐P13 and infliximab originator in IBD shows similar epitope recognition—evidence from basic science supports safe switching to biosimilars. Issue 5 (9th August 2018) - Pouillon, L.; Allocca, M.; Peyrin‐Biroulet, L.
Abstract : Linked Content This article is linked to Goncalves et al papers. To view these articles visithttps://doi.org/10.1111/apt.14808 andhttps://doi.org/10.1111/apt.14860 .